Financial Performance Analysis of the Department of Culture (Kundha Kabudayan) of Gunungkidul Regency in the Management of the Regional Revenue and Expenditure Budget (APBD) for the Years 2019–2024 - Putri, Intan Yulia; Santoso, Fahrul Imam (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
The development of culture in Gunungkidul Regency has flourished thanks to the Special Autonomy Fund, which supports the preservation, development, and utilization of local culture through the preservation of historical sites, the revitalization of traditional arts, and community-involved activities. The achievement of budget realization, as reflected in the Budget Realization Report of Regional Revenue and Expenditure (APBD) from 2019 to 2024, has shown fluctuations. This research aims to evaluate the financial performance of the Cultural Affairs Office of Gunungkidul Regency for the fiscal years 2019–2024. This study employs a qualitative approach, utilizing data collection methods such as observation, documentation, and interviews. The data used consist of primary data obtained from interviews with the staff of the Cultural Affairs Office of Gunungkidul Regency, as well as secondary data from the Budget Realization Report of Regional Revenue and Expenditure (APBD) for 2019–2024. The research focuses on analyzing the financial performance ratios, including efficiency ratios, effectiveness ratios, expenditure variance ratios, expenditure growth ratios, and SILPA (Remaining Budget Balance) ratios. The results indicate that the financial performance of the Cultural Affairs Office of Gunungkidul Regency, as measured by efficiency ratios, effectiveness ratios, and variance analysis, is generally good, with positive expenditure growth and a declining SILPA ratio. However, this study also finds that the effectiveness ratio is still relatively low. These findings are expected to provide valuable input for the Cultural Affairs Office of Gunungkidul Regency. There is a need for capacity building for human resources and the utilization of technology for monitoring and evaluation to ensure optimal budget implementation.